The double burden of COVID-19 and cancer at the Uganda Cancer Institute - Natalie Anumolu; Matida Bojang; Pius Mulamira; Courtney Jankowski; Kia Lechleitner; Sarah Abunike; Simon Kasasa; Robert Lukande; Nixon Niyonzima; Kirsten Beyer (Inishmore Laser Scientific Publishing Ltd, 2024)
# Background Cancer is increasingly diagnosed in Africa, with more than one million new diagnoses annually. In Uganda, the Uganda Cancer Institute (UCI) is the primary cancer care facility, with patients travelling long distances to this facility to receive care. During the COVID-19 pandemic, cancer care was disrupted on several levels, including prevention, screening, diagnosis, treatment, and follow-up. National lockdowns impeded patient access to UCI and halted cancer screening. # Methods This study used qualitative interviews to obtain primary data from professionals working at UCI. Interviews were conducted from April 2022 to January 2023. KI (key informants) 's were purposively selected, identified by colleagues at UCI and recruited through email and WhatsApp messaging. Verbal consent was obtained. Thirty to 60-minute open-ended interviews conducted virtually and in person were audio recorded and transcribed verbatim. Transcripts were coded via MAXQDA software and analyzed to identify themes. # Results Thematic analysis revealed three major challenges to cancer care during COVID-19. First, UCI experienced logistical barriers such as travel restrictions, staff shortages, and insufficient protective gear. Second, staff adapted to the inflexible national lockdown policy for chronic health care with modifications to treatment regimens. Third, KI reported a significant mental health burden and reflected on how care should be improved. # Conclusions As colleagues got infected, UCI staff organized their training, discussed treatment plans with colleagues, and continued to care for patients at personal risk. Resilience characterized UCI's response to COVID-19. They adapted treatment protocols to their setting, many of which remain the standard of care today. At the same time, there is a need for capacity building tailored to the Ugandan context to provide cancer care effectively in case of another pandemic.